Repeated selection of supplier, factors and results: the Czech Republic. Issue 4 (4th November 2019) - Plaček, Michal; Schmidt, Martin; Ochrana, František; Vaceková, Gabriela; Soukopová, Jana
Abstract : Purpose: The paper aims to deal with the analysis of the factor leading to the repeated selection of the specific supplier and the effect of this recurrent selection on overpricing of public contracts. Design/methodology/approach: A mix of quantitative and qualitative methods is used to achieve this goal. To analyze the chances of obtaining repeated contracts, the logistic regression method is used. To analyze the factor of overpriced contracts, the classic ordinary least squares regression model is used. The focus group method is then used to explain the factors acting on the part of the contracting authorities. Findings: The results show that the prior procurement of a given contracting authority, or work for the public sector in general, has a statistically significant effect on the conclusion of contracts. The use of less-transparent forms of input has a strong impact. The non-transparent selection of suppliers rather than repetition of contracts generally results in the over-pricing of contracts. The IT sector is an exception. Social implications: This research is also essential for real public policy. Given the amount of GDP allocated to the public procurement market, it makes sense to continually seek room for improvement. Here is an attempt to find this by examining the contracting authorities' behavior when awarding repeated contracts. Originality/value: This research is original because it looks at the problem of the contracting authority in the wider context and optics of the path dependency theory, which has not yet been applied to the public procurement environment. The focus is also on IT procurement, which according to this study has not been empirically investigated in this way, is also innovative.